Are Green, dense cities more inclusive? Densification and housing accessibility in Oslo. Issue 10 (3rd October 2021) - Cavicchia, Rebecca
ABSTRACT: Planning policies in Europe and elsewhere increasingly promote urban densification as the spatial planning solution for achieving urban sustainability goals. However, examples from several cities have shown the complexity, in practice, of translating densification's potentials for creating environmentally, socially and economically sustainable compact cities. Although extensive research is already available on the sustainability dimensions of densification, the social dimension has, in general, been under-researched. Specifically, spatial associations between densification and its potential social impacts have received little attention. This paper aims at contributing to filling this gap. The aim is twofold: first, I analyse overlapping spatial patterns of densification and housing accessibility, which I consider to be an indicator of social sustainability; second, I explore mechanisms that may hinder the possibility of combining urban densification with an inclusive housing offer. The findings are based on a mixed-method approach, consisting of a quantitative assessment of housing accessibility and a spatial and policy analysis of urban densification. Using Oslo as a case study, I argue that, in a context where the market rules the planning system and housing policies, densification may eventually compound market logics and exacerbate social exclusion dynamics.